Telehealth intervention involving the HEARTS Technical Package and the additional use of an activity monitor to increase physical activity level post-stroke: Protocol for a feasibility randomized controlled trial - Paula da Cruz Peniche; Olive Lennon; Jordana de Paula Magalhães; Jéssica Melo dos Santos; Janaine Cunha Polese; Christina Danielli Coelho de Morais Faria (PLoS ONE, 2025)
Background Low physical activity level is a common risk factor for recurrent stroke. Feasibility studies show behavior change interventions can increase physical activity participation, but face barriers (e.g., home visits or internet access). Low-cost telehealth approaches, like telephone calls, may overcome these challenges. Another low-cost strategy involves motivational tools supporting “Behavioral Regulation,” such as physical activity monitors. However, evidence is insufficient to support their use in increasing physical activity levels post-stroke. A systematic review suggests integrating these devices into multifaceted behavior change interventions (e.g., the 5As brief intervention outlined in the HEARTS Technical Package) may enhance their effectiveness. Combined with physical activity monitors and telephone follow-up, this approach has proven feasible for individuals post-stroke. These findings underscore the need to explore combining the 5As brief intervention with physical activity monitors to assess potential added benefits. This feasibility randomized controlled trial (RCT) study will investigate whether the telehealth intervention (by telephone call) combining the 5As brief intervention, as outlined in the HEARTS Technical Package, and physical activity monitoring, compared to a control group receiving only the 5As brief intervention, is feasible and supports a fully powered RCT. Methods A feasibility RCT study, with blinded assessment, will assign 24 individuals post-stroke (diagnosed ≥ 6 months), aged ≥ 18 years, inactive, able to walk 10 meters independently, and medically approved for physical activity, to experimental (n = 12) or control group (n = 12). Both groups will undergo the 5As brief intervention (Ask, Advise, Assess, and Assist delivered face-to-face, and Arrange via telephone call follow-up), for 12 weeks, with the experimental group also using a physical activity monitor. Outcomes include feasibility of recruitment, intervention, measurement, and blinding the outcome assessor, cost and clinical outcomes. Discussion The intervention aligns with stroke secondary prevention recommendations and utilizes low-cost telehealth approaches. This study will contribute to defining future RCT phases. Trial registration ClinicalTrials.gov NCT06068036.